The effect of calcium supplement intake on lipid profile: a systematic review and meta-analysis of randomized controlled clinical trials. Issue 8 (10th March 2022) - Derakhshandeh-Rishehri, Seyedeh-Masomeh; Ghobadi, Saeed; Akhlaghi, Masoumeh; Faghih, Shiva
Abstract: Despite the potential role of dietary calcium in fat excretion, the favorable effects of calcium supplements on lipid profile remains inconclusive. The current study aimed to review the effect of calcium supplement intake on lipid profile in randomized controlled clinical trials (RCTs). This systematic review and meta-analysis was conducted in PubMed, Scopus, Embase, and Central. RCTs which assessed the effects of calcium supplementation on lipid profile were included. All outcomes were recorded as continuous variables, and the effect size was measured. We classified studies according to dose of supplement, study duration, and dyslipidemia. Calcium supplement intake was associated with a significant reduction in low density lipoprotein cholesterol (LDL-C) level (WMD:-0.08; 95%CI:-0.16, -0.01)(mmol/l), especially with intakes of at least 1000 mg/day (WMD:-0.13; 95%CI:-0.23, -0.03)(mmol/l), with intakes of at least 12 weeks (WMD:-0.08; 95%CI: −0.16, -0.00)(mmol/l), and in individuals without dyslipidemia (WMD:-0.15; 95%CI:-0.26, -0.04)(mmol/l). Also, in another subgroup analysis, consumption of less than 1000 mg/day calcium supplement caused a significant increase in Total Cholesterol (TC) level (WMD: 0.24; 95%CI: 0.05, 0.42) (mmol/l). In other blood lipids or study subgroups we observed no significant effect. We concluded that calcium supplements had a favorable effect on LDL-C level, especially in individuals without dyslipidemia, higher calcium intakes, and longer period of consumption.